Characterization and Classification of the Soils of Brahmanakotkur Watershed in Kurnool District of Andhra Pradesh - K.V. Ramana, V. Munaswamy, G. Prabhakara Reddy3 and P. Sudhakar, S. Satish, M.V.S. Naidu (Journal of the Indian Society of Soil Science, 2019)
Eleven typical pedons representing major landforms in semi-arid ecosystem of Brahmanakotkur watershed in Kurnool district of Andhra Pradesh viz., plains and uplands originated from limestone, dolomite, quartzite and shale parent materials under varying land uses were studied for their morphological characteristics, physical and chemical properties, soil genesis and taxonomy. The soils were neutral to strongly alkaline (pH 7.01 to 8.86) in reaction, non-saline (EC 0.10 to 0.58 dS m-1), shallow, deep and very deep in depth and had isohyperthermic temperature and ustic soil moisture regimes. The texture, organic carbon (OC), cation exchange capacity (CEC) and base saturation were ranged from gravelly sandy loam to clay, 0.10 to 5.8 g kg-1, 8.11 to 61.72 cmol(p+)kg-1 and 69.1 and 99.1%, respectively. Pedon 11 was placed under Entisol due to absence of sub-surface diagnostic horizon and was classified as Lithic Ustorthent whereas pedons 4, 8 and 9 were grouped under Inceptisol due to presence of cambric (Bw) sub-surface diagnostic horizon and classified as Lthic Haplustept and Typic Haplustept. However, the remaining pedons were placed under Vertsiol due to presence of more than 30% clay in all the horizons, slickensides and wedge shaped aggregates in sub-surface horizons and cracks in surface horizons and were classified as Typic Haplustert, Sodic Haplustert, Typic Calciustert and Leptic Calciustert.